CORRELATION BETWEEN READING INTERESTS AND INDONESIAN LANGUAGE LEARNING OUTCOMES TO FIFTH GRADE STUDENTS OF PUBLIC ELEMENTARY SCHOOLS IN PEJAGOAN SUB-DISTRICT IN ACADEMIC YEAR OF 2019/2020 - Ajiningrum Putri Ayu Dirgantari; Joharman Joharman; Ngatman Ngatman (Universitas Sebelas Maret, 2020)
AbstractThe objectives of the research were to prove significant and positive correlation between reading interests and Indonesian language learning outcomes and to determine the contribution of reading interests on Indonesian language learning outcomes to fifth grade students in Pejagoan Sub-District in academic year of 2019/2020. The research was quantitative correlational study. The prerequisite test used the normality and linearity test. The data analysis included simple correlation test and adjusted R square with significance level of 5%. The results indicated that there was positive and significant relationship between reading interests and Indonesian language learning outcomes. The correlation was 0.539 and Adjusted R square of reading interests on Indonesian language learning outcomes was 22.62%. It concludes that there is significant and positive correlation between reading interests and Indonesian language learning outcomes to fifth grade students in Pejagoan sub-District in academic year of 2019/2020.